Direct Oxidation of Aldehydes to Methyl Esters with Urea Hydrogen Peroxide and p-Toluenesulfonyl Chloride - Jeong, Deuk J.; Lee, Su Bin; Lee, Jong Chan (Letters in Organic Chemistry, 2017)
Combination of urea hydrogen peroxide and p-toluenesulfonyl chloride in methanol was proved to be facile and highly efficient for the oxidative methyl esterification of various aldehydes to the corresponding carboxylic methyl esters.
Keywords: esters